2013
DOI: 10.5114/aoms.2012.30952
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid volumes and iodine status in Egyptian South Sinai schoolchildren

Abstract: IntroductionThe determination of goitre prevalence in children by ultrasonography is an important tool for considering iodine deficiency disorders. Our objective was to describe measurements of thyroid volumes by ultrasonography in Egyptian South Sinai schoolchildren and compare these with the WHO/International Council for the Control of Iodine Deficiency Disorders normative thyroid volume criteria (WHO/ICCIDD).Material and methodsCross-sectional thyroid ultrasonographic data of 719 schoolchildren (339 boys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The high rate of exophthalmos noted in this study could be due to the high incidence of goiter secondary to iodine deficiency reported in South Sinai. 26 Significant improvement in visual impairment prevalence (p50.0001) occurred when eyeglasses were prescribed, prepared and delivered to any child having one or both eyes with VA56/12. WHO guidelines state that most individuals with presenting VA56/18 and !3/60 require spectacles, surgery (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The high rate of exophthalmos noted in this study could be due to the high incidence of goiter secondary to iodine deficiency reported in South Sinai. 26 Significant improvement in visual impairment prevalence (p50.0001) occurred when eyeglasses were prescribed, prepared and delivered to any child having one or both eyes with VA56/12. WHO guidelines state that most individuals with presenting VA56/18 and !3/60 require spectacles, surgery (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Results obtained in this way (Table I) erroneously suggest that there is still goitre endemicity in the study population. The fact that the reference data were developed based on examinations carried out in a supine position may be the possible cause of this inconsistency [14, 20, 21]. Such a discrepancy may also result from different methods of measurement and associated inter-observer and intra-observer errors [20].…”
Section: Discussionmentioning
confidence: 99%
“…South Sinai was selected for the present work as it has the highest prevalence of goiter in Egypt (Yamamah et al 2013) and many skin diseases were also reported to be prevalent (Yamamah et al 2012). Within S.Sinai, children of Ras Sidre were reported to have the highest prevalence of both groups of diseases.…”
Section: Discussionmentioning
confidence: 99%
“… Study design: Prospective cohort study.  Study site: Ras Sidre district was selected as it has the highest prevalence of goiter accounting for 20.0% (Yamamah et al 2013). It also has the highest rates of skin diseases among S.Sinai children (Yamamah et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation